Leader ethical voice and subordinate job performance: the chain mediating role of subordinate identification with leader and leader-member exchange - Xia, Fubin; Lu, Ping; Wang, Lifang (Frontiers in Psychology, 2024)
The chain mediating role of subordinate identification with leader and leader-member exchange" to be considered for publication in Frontiers in Psychology.Ethical voice refers to the open discussion and opposition of unethical issues and phenomena within an organization by its members, which challenge and change the organization's unethical behaviors, procedures, and policies. It is a valuable ethical behavior that helps organizations timely identify and address existing unethical problems and practices, thereby avoiding serious issues and crises. This study explores how leader's ethical voice affects subordinates' job performance and reveals the underlying mechanisms. This study makes two contributions. Firstly, it advances the understanding of the effects of leader's ethical voice and enriches the field of ethical voice research. Secondly, it uncovers the multiple underlying mechanisms through which leader's ethical voice influences subordinates' job performance, contributing to the understanding of how leaders can enhance organizational efficiency through their ethical behavior. These contributions are of great significance in comprehensively and deeply understanding the effectiveness of leader's ethical voice, innovating leadership ethics theories, and promoting organizational ethical practices.We believe that this article will be of great interest to your readers because it focuses on an interesting and novel topic in leader's ethical voice research, and provides valuable insight into the moral compensatory effects of leader's ethical voice on subordinates' job performance.